The Impact of Human Resource Development on Student Satisfaction with the Academic Information System at Higher Education Institutions - Isyfi Agni Nukhbatillah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
This study was guided by the development of human resources in the field of digital services for academic information systems at STITNU Al-Farabi Pangandaran. According to Gouzali, the development of human resources in an organization aims to ensure that the knowledge, abilities, and skills of human resources are in line with the demands of their work. The purpose of this study is to determine the extent of the influence generated by human resource development activities (independent variable) by assessing the three indicators of knowledge, ability, and skill on student satisfaction with the academic information system at STITNU Al-Farabi Pangandaran (dependent variable). The method used in this study is quantitative, employing survey techniques. The population in this study consists of active students in the 2021-2024 academic year in the MPI, PIAUD, BKPI, MBS, and HKI programs. The sampling technique used in this study is proportionate stratified sampling, with a sample size of 73 students. Data collection in this study was conducted using interviews, skala likert questionnaires, and documentation. Data analysis techniques included simple linear regression tests, determination coefficient tests, and t-tests using SPSS version 26. The analysis results showed a positive and significant influence between human resource development and student satisfaction with the academic information system, with a correlation coefficient of 0.798. The calculated results obtained by the researcher show that the calculated t-value is greater than the table t-value (11.173 > 1.993). Therefore, it can be concluded that H0 is rejected and Ha is accepted, meaning that there is an influence of human resource development (independent) on student satisfaction with the academic information system (dependent). The percentage of influence is 63.7%, while 36.3% is influenced by other factors not examined by the researcher.